2009
DOI: 10.1155/2009/595126
|View full text |Cite
|
Sign up to set email alerts
|

Chitosan‐Alginate Sponge: Preparation and Application in Curcumin Delivery for Dermal Wound Healing in Rat

Abstract: A biodegradable sponge, composed of chitosan (CS) and sodium alginate (SA), was successfully obtained in this work. The sponge was ethereal and pliable. The chemical structure and morphology of the sponges was characterized by FTIR and SEM. The swelling ability, in vitro drug release and degradation behaviors, and an in vivo animal test were employed to confirm the applicability of this sponge as a wound dressing material. As the chitosan content in the sponge decreased, the swelling ability decreased. All typ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

5
91
2
2

Year Published

2012
2012
2023
2023

Publication Types

Select...
5
4
1

Relationship

0
10

Authors

Journals

citations
Cited by 152 publications
(100 citation statements)
references
References 31 publications
5
91
2
2
Order By: Relevance
“…An immatured granulation tissue with many inflammatory cells and congested vessels were observed in gauze treated groups, granulation tissue and collagen alignment were more advanced in C2A2, C2A2-curcumin sponge treated wounds. Arrangement of collagen is loose in control wounds and compact in C2A2 treated wounds [60]. In the previous reported in vitro and in vivo studies, curcumin was exposed as a potential anti-inflammatory, antimicrobial, antioxidant, and accelerated wound healing activities [61][62][63].…”
Section: Wound Dressings With Chitosan and Natural Polymersmentioning
confidence: 98%
“…An immatured granulation tissue with many inflammatory cells and congested vessels were observed in gauze treated groups, granulation tissue and collagen alignment were more advanced in C2A2, C2A2-curcumin sponge treated wounds. Arrangement of collagen is loose in control wounds and compact in C2A2 treated wounds [60]. In the previous reported in vitro and in vivo studies, curcumin was exposed as a potential anti-inflammatory, antimicrobial, antioxidant, and accelerated wound healing activities [61][62][63].…”
Section: Wound Dressings With Chitosan and Natural Polymersmentioning
confidence: 98%
“…The chitosan was responsible for the swelling reduction and wound healing, at the same time as the curcumin influenced the increasing growth of collagen and other connecting tissues 17,18 .…”
Section: Introductionmentioning
confidence: 99%
“…Previous research stresses the importance of biochemical modification of biomaterial in tissue repair and regeneration [1]. Recent studies have shown that physical factors played important role in regulating cellular behavior [2].…”
mentioning
confidence: 99%